Integrating Constitutional Mandates and Sharia Values: A Holistic Approach to the Handling of Abandoned Children by the Banda Aceh Social Services Department - Yamin, Ashabul; Yuhermansyah, Edi; Hanapi, Agustin (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2026)
Abandoned children remain a crucial social issue in Indonesia, including in the city of Banda Aceh. The high prevalence of abandoned children is generally triggered by complex factors, such as the death of parents, high divorce rates, structural poverty, and limited access to education. Based on 2024 data, there are approximately 53 abandoned children in Banda Aceh requiring specialized intervention. In response to this issue, this study aims to examine in depth how the Banda Aceh City Government interprets the mandate of Article 34, Paragraph (1) of the 1945 Constitution of the Republic of Indonesia as the constitutional foundation for handling abandoned children, and how this interpretation is manifested through policy formulation and operational measures in the field. This research employs a juridical-empirical method with a case study design. Data analysis was conducted through a review of positive legal norms and observations of social service practices by the Social Services Department (Dinas Sosial). The results indicate that the local government interprets the constitutional provision as an absolute state obligation to provide care, protection, and the fulfillment of basic needs for abandoned children. Operationally, this implementation is realized through a series of systematic stages: starting from proactive outreach mechanisms, rapid assessments to identify conditions, and temporary guidance at the Lamjabat Halfway House (Rumah Singgah Lamjabat), to intensive inter-agency coordination aimed at family reunification and child repatriation. This case study demonstrates that the constitutional mandate has been effectively implemented in Banda Aceh. However, field execution still faces several challenges, particularly regarding human resource constraints, minimal budget allocation, and a lack of supporting infrastructure. Consequently, strengthened synergistic collaboration across sectors is essential to ensure that the state's fundamental responsibility for the protection of abandoned children is fulfilled optimally.